Inovasi Pupuk Bokashi untuk Pemberdayaan UMKM Peternakan di Desa Ngrendeng - Denata, Hesti Eka; Utami, Hapsari Wiji; Rahmawati, Sustania; Ma’ruf, Muhammad Muizzul; Faradhita, Amanta Tiara; Nuriza, Irrandy Andhana; Inayah, Khozinatul; Burhanuddin, Fahmi Septiano; Ekaputri, Dinti (Ali Institute of Research and Publication, 2025)
Ngrendeng Village in Ngawi Regency, East Java, has great potential for goat farming, which produces a large amount of fecal waste. Without proper management, this waste can pollute the environment and pose health risks. The purpose of this study is to introduce a new method of converting goat waste into bokashi fertilizer, which serves as an environmentally friendly solution and a strategy to promote small and medium enterprises (SMEs) in the livestock sector. Using the Participatory Learning and Action (PLA) approach, 35 participants (farmers and SME actors) took part in a one-day training session on July 7, 2025. The training included hands-on practice, interactive discussions, and extension activities. During three weeks of fermentation, an average of 150 kilograms of bokashi was produced per batch. Participants’ knowledge scores increased by 42% (pre–post test, p < 0.05), and an estimated 30% reduction in monthly chemical fertilizer costs was achieved. The results indicate that the bokashi innovation not only improves waste management and soil fertility but also strengthens local economic independence through new business opportunities. Therefore, this innovation serves as a strategic step toward sustainable agriculture and the empowerment of SMEs based on local potential.